(untitled) (Contemporary Issues in Social Sciences and Management Practices, 2023)
Since the middle of the 1990s, Pakistan and the Taliban have maintained a positive relationship. Pakistan’s aggressive actions as Afghanistan’s eastern neighbor have contributed to the Taliban’s recent takeover. After the Afghan government left office, there was a rise in anti-Pakistan sentiment. It is likely that India will end its structural presence and turn its borders against Pakistan. This study seeks to offer a thorough analysis of the effects of Pakistan’s post-Taliban rule in Afghanistan. Pakistan is in a precarious position as a result of Afghanistan’s quickly changing scenario and worries that terrorist bloodshed would increase if the Taliban are unable to unite other Afghan ethnicity and political parties to form a strong and stable government. For stability and peace in the region, Afghanistan must be stable as the peaceful, prosperous and stable Afghanistan ensures the collective security and stability of a whole South Asia and in particular, Pakistan. Moreover, the study put emphasis on the fact that Indian unnecessary involvement in Afghanistan is acting as a trouble maker to bring peace and stability in Afghanistan. Under the Taliban regime it is more likely that Indian involvement in Afghanistan will be minimized. Secondly when it comes to the geopolitical competition, international powers, in particular China and America will need to act wisely in the international affairs of South Asia.